HUBUNGAN KEMAMPUAN KOMUNIKASI INTERPERSONAL DENGAN KEPERCAYAAN DIRI PADA ANAK USIA 5-6 TAHUN DI TK BINTANG MULYA KECAMATAN TAMBANG - Oktaviyani, Yola; Novianti, Ria; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The objectives of this study were: 1) To find out interpersonal communication skills in children aged 5-6 years at TK Bintang Mulia, Tambang District, Kampar Regency. 2) To determine self-confidence in children aged 5-6 years at Bintang Mulia Kindergarten, Tambang District, Kampar Regency. 3) To find out the relationship between interpersonal communication skills and self-confidence in children aged 5-6 years at TK Bintang Mulia, Tambang District, Kampar Regency. So the problem can be formulated in this study are: 1) What is the interpersonal communication skills in children aged 5-6 years at TK Bintang Mulia District of Tambang, Kampar Regency? 2) How is self-confidence at an early age in children aged 5-6 years at TK Bintang Mulia District of Tambang, Kampar Regency? 3) Is there a relationship between interpersonal communication and self-confidence in children aged 5-6 years at TK Bintang Mulia District of Tambang, Kampar Regency? The place of this research was carried out at Bintang Mulya Kindergarten, Tambang District, Kampar Regency. The time of this study began in August 2018 until the research phase in January 2019. The sample of this study was 42 children aged 5 - 6 years at TK Bintang Mulia District of Tambang, Kampar Regency. Based on the results of the study, conclusions can be drawn: 1) Children aged 5-6 years in TK Bintang Mulya Subdistrict Tambang have quite good interpersonal communication skills. 2) Children aged 5-6 years in TK Bintang Mulya Kecamatan Tambang have fairly good self-confidence. 3) There is a relationship between interpersonal communication skills and self-confidence in children aged 5-6 years in Bintang Mulya Kindergarten, Tambang District. The results of the calculation of correlation using product moment correlation obtained rxy value of 0.440. The relationship between interpersonal communication skills and self-confidence in children aged 5-6 years in TK Bintang Mulya, Tambang sub-district was 19.4%.Key Words: interpersonal communication, confidence.